2021
DOI: 10.1186/s40561-021-00174-7
|View full text |Cite
|
Sign up to set email alerts
|

The virtual COVID-19 classroom: surveying outcomes, individual differences, and technology use in college students

Abstract: The COVID-19 pandemic caused many colleges to quickly shift to virtual learning, leading students to rely on technology to complete coursework while also experiencing new situations and stressors. The present study explored students’ technology use in their online course in conjunction with several student outcomes and individual difference measures. Ninety-six undergraduate students were surveyed about devices used and their perceptions of those devices. In addition, the survey measured students’ engagement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
1
11
0
2
Order By: Relevance
“…Over the last two decades or so, VC learning has expanded around the globe (e.g., Keengwe & Kidd, 2010 ; Kemp & Grieve, 2014 ; Manegre & Sabiri, 2022 ; Palvia et al, 2018 ; Sage et al, 2021 ) and the COVID-19 situation has considerably accelerated educational institutions’ implementation of VC classes. Researchers have identified various paybacks for VC classes and one of the most significant benefits is its flexibility that allowing students make decisions about when and what they learn (Keengwe & Kidd, 2010 ; Kemp & Grieve, 2014 ).…”
Section: Research In Vc Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades or so, VC learning has expanded around the globe (e.g., Keengwe & Kidd, 2010 ; Kemp & Grieve, 2014 ; Manegre & Sabiri, 2022 ; Palvia et al, 2018 ; Sage et al, 2021 ) and the COVID-19 situation has considerably accelerated educational institutions’ implementation of VC classes. Researchers have identified various paybacks for VC classes and one of the most significant benefits is its flexibility that allowing students make decisions about when and what they learn (Keengwe & Kidd, 2010 ; Kemp & Grieve, 2014 ).…”
Section: Research In Vc Learningmentioning
confidence: 99%
“…It was the only way forward to allow students to continue learning during the lockdown period. Many studies (Ali, 2019 ; Farkhani et al, 2022 ; Sage et al, 2021 ; Sprenger & Schwaninger, 2021 ; Yaakub, 2020 ) have shown that virtual learning is the way to partake in online education amidst the hypercharge and great challenges in the world today for countries to thrive, transform, and ensure sustainability. It has been an officially recognized platform for filling in the gaps of traditional classroom teaching–learning approaches and it has rightly argued that VC has blurred the boundaries of face-to-face classroom teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Distance education has made universities perceive the need to use different applications and media to make the teaching process more effective and viable. As mentioned by Sage et al (2021), during confinement many education centers quickly ventured into small classes. Students and teachers faced new challenges and experiences that they can benefit from thanks to tools.…”
Section: Resultsmentioning
confidence: 99%
“…This inclusion was a necessity to face new challenges like lack of interest, short attention spam, and a society fully absorbed in that same technology. So as the use of tablets, computers, smartphones, messaging apps, social networks, and YouTube have become a daily basis aspect of our lives, it is almost impossible to conceive education without them [33]. Nonetheless, adopting them correctly was a reality only for the few which went step by step in that direction.…”
Section: Education In Pandemic Timementioning
confidence: 99%